IMPLEMENTASI KONSEP PENDIDIKAN ISLAM DALAM STRATEGI BRANDING LEMBAGA PENDIDIKAN - Listari, Tiara; Annur, Saipul; Baharuddin, Baharuddin (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Islamic education is an educational system grounded in the values of the Qur’an and the Sunnah, aiming to develop individuals who are faithful, knowledgeable, and possess noble character through a balanced integration of spiritual, intellectual, social, and moral dimensions. In the era of globalization and modernization, Islamic educational institutions face challenges such as increasing competition in educational quality, growing public demands for excellent educational services, and the need to build a positive and trustworthy institutional image. These conditions require Islamic educational institutions not only to excel in internalizing Islamic values but also to implement professional branding strategies without compromising their Islamic identity. This study aims to examine the concept of Islamic education and analyze relevant and applicable branding strategies for Islamic educational institutions in the modern era. The research employs a qualitative approach using library research by analyzing various literature sources, including books, scholarly journals, and academic articles related to Islamic education and educational branding. The findings indicate that integrating Islamic educational concepts with branding strategies grounded in Islamic values can enhance institutional image, strengthen public trust, and improve the sustainable competitiveness of Islamic educational institutions. ABSTRAK Pendidikan Islam merupakan sistem pendidikan yang berlandaskan nilai-nilai Al-Qur’an dan As-Sunnah dengan tujuan membentuk insan yang beriman, berilmu, dan berakhlak mulia secara seimbang antara aspek spiritual, intelektual, sosial, dan moral. Di era globalisasi dan modernisasi, lembaga pendidikan Islam menghadapi tantangan berupa persaingan mutu, tuntutan masyarakat terhadap kualitas layanan pendidikan, serta kebutuhan membangun citra lembaga yang positif dan terpercaya. Kondisi ini menuntut lembaga pendidikan Islam untuk tidak hanya unggul dalam internalisasi nilai-nilai keislaman, tetapi juga mampu menerapkan strategi branding yang profesional tanpa menghilangkan identitas keislamannya. Penelitian ini bertujuan untuk mengkaji konsep pendidikan Islam serta menganalisis strategi branding yang relevan dan aplikatif bagi lembaga pendidikan Islam di era modern. Metode penelitian yang digunakan adalah pendekatan kualitatif dengan jenis studi kepustakaan (library research) melalui analisis berbagai sumber literatur berupa buku, jurnal ilmiah, dan artikel akademik yang berkaitan dengan pendidikan Islam dan branding pendidikan. Hasil kajian menunjukkan bahwa integrasi konsep pendidikan Islam dengan strategi branding yang berlandaskan nilai-nilai Islam mampu meningkatkan citra lembaga, memperkuat kepercayaan masyarakat, serta meningkatkan daya saing lembaga pendidikan Islam secara berkelanjutan.